2003
DOI: 10.1590/s0031-10492003000500001
|View full text |Cite
|
Sign up to set email alerts
|

<![CDATA[<b>Faunistic survey of sandstone caves from Altin?polis region, </b><b>S?o Paulo State</b><b>, </b><b>Brazil</b>]]>

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This study represents the first comprehensive checklist of herpetofauna compiled for the Itambé cave and waterfall region (Table 1), which serves as an ecotone between the Cerrado and the Atlantic Forest and is a popular destination for ecotourism. We could not find any previous studies specifically focused on the study area, except for a 2003 study conducted in the "Vale das Grutas" of Altinópolis, which solely examined the caves without considering the surrounding vegetation (ZEPPELINI FILHO et al, 2003). The previous study reported no amphibian or lizard species but documented two snake species (Bothrops sp.…”
Section: Resultsmentioning
confidence: 99%
“…This study represents the first comprehensive checklist of herpetofauna compiled for the Itambé cave and waterfall region (Table 1), which serves as an ecotone between the Cerrado and the Atlantic Forest and is a popular destination for ecotourism. We could not find any previous studies specifically focused on the study area, except for a 2003 study conducted in the "Vale das Grutas" of Altinópolis, which solely examined the caves without considering the surrounding vegetation (ZEPPELINI FILHO et al, 2003). The previous study reported no amphibian or lizard species but documented two snake species (Bothrops sp.…”
Section: Resultsmentioning
confidence: 99%
“…Only a small part of them have been sampled (about 50 caves), which revealed more than 500 invertebrate species. Furthermore, 20 caves presented at least two troglobitic species (Dessen et al 1980, Trajano and Gnaspini-Netto 1991, Trajano and Moreira 1991, Gnaspini-Netto and Trajano 1994, Pinto-da-Rocha 1995, Lourenço et al 2004, Zeppelini et al 2003, Bichuette et al 2008, Alves et al 2011, Souza-Silva et al 2011, Bertani et al 2013, Fernandes and Bichuette 2013, Gallão and Bichuette 2015, Pellegrini et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the authors found 37 species with troglomorphic traits in 11 caves in the area, which represent 23% of the total invertebrates sampled (160 species). Zeppelini et al (2003) studied nine sandstone caves in the Northern region of the state of São Paulo, Brazil, and found 83 morphotypes (10 species/cave, sd= 10) for an average cave extension of 373 m (sd= 246).…”
Section: Introductionmentioning
confidence: 99%